Chemical composition of groundwater in capital city Bhubaneswar, Odisha - PAUL, J. C.; PANIGRAHI, B (Journal of Soil and Water Conservation, 2020)
In this study, ground water samples were collected for two years i.e. 2010 and 2011 from the monitoring wells of 30 different places in the study area of capital city of Bhubaneswar, Odisha. Water samples were analyzed for major ions and toxic metals using standard techniques in laboratory. Different chemical composition like pH, total dissolved solids (TDS), electrical conductivity (EC), values of cations like sodium, potassium, magnesium and calcium, values of anions like bicarbonate, sulphate, chloride, nitrate, fluoride and iron of groundwater of all the 30 places were determined for both the years. Presence of different heavy metals like manganese (Mn), chromium (Cr), cadmium (Cd) and lead (Pb) in the groundwater samples of various places were also determined. The pH of the groundwater is near neutral to slightly basic, with an apparent increase in the year 2011 as compared to 2010. In the year 2010, EC value varied between 111 to 956 Î¼mhos/cm while in the year 2011 it varied between 132 to 980 Î¼mhos/ cm. Study of different water quality parameters in both the years including pH, TDS, EC, different anions and cations, iron and fluoride as well as heavy metals indicate that ground water is safe for drinking in almost all places in Bhubaneswar. To understand the water quality and utilitarian aspects of groundwater, the chemical indices of Sodium Adsorption Ratio (SAR) were further calculated and compared with the limits given by WHO. It was observed that the quality of groundwater is suitable for drinking and irrigation purpose in the study area.